P354 Refinement and confirmation of psychometric properties of the Inflammatory Bowel Disease Distress Scale (IBD-DS): A new tool to measure disease-specific distress. (16th January 2018) - Dibley, L; Czuber-Dochan, W; Woodward, S; Wade, T; Bassett, P; Sturt, J; Norton, C; ,
Abstract: Background: We previously reported initial development and psychometric properties of the Inflammatory Bowel Disease Distress Scale (IBD-DS), 1 guided by recommended procedures. 2, 3 Statistical analysis following test–retest indicated considerable item reduction was possible, reducing the length of the questionnaire by 50%. A further validation round to confirm construct validity and reliability (repeatability) of the scale, and identify any domains within the newly reduced draft scale, was therefore indicated. Methods: We recruited a cohort of community-dwelling patients with IBD via the social media platforms and the website of a UK-based IBD charity. Participants received the revised shorter IBD-DS, the relevant disease activity index (Harvey Bradshaw Index [HBI]) for CD, Simple Clinical Colitis Activity Index [SCCAI]) for UC, and the Hospital Anxiety and Depression Score (HADS) on two occasions, approximately 2 weeks apart. Internal consistency was assessed using Cronbach's alpha; intra-class correlation was used to examine repeatability. Factor analysis with varimax rotation was used to assess domains within the scale. Results: 209 people volunteered to receive the 28-item IBD-DS; 123 (58.8%) returned the test round, and 95 (77%) returned the retest round. Higher IBD-DS values were associated with higher values on the HBI, SCCAI, and HADS (all p < 0.001). Cronbach's alpha was 0.95. Ninety-five participants had complete data and stable disease. An ICC value of 0.92 (95% CI, 0.88, 0.95) indicated fairly good to excellent agreement between test and retest values. Factor analysis identified four domains; one explained almost half of all variation in the data, indicating that a single domain with an overall score (range 0–168, plus three supplementary unscored items) is appropriate. Conclusions: The IBD-DS performs well psychometrically. It offers a useful clinical and research tool for assessing IBD distress. Further testing, to include responsiveness to change, relationship with self-management activity such as drug concordance, and determining cut-off points, is needed. References: 1. Dibley L, Czuber-Dochan W, Woodward S, et al. Distress in IBD: development of a new assessment tool, 11th Congress of ECCO, Amsterdam, The Netherlands, 15–19 March 2016. 2. Centre for Drug Evaluation and Research. Guidance for industry. Patient reported outcome measures: use in medical product development to support labelling claims. 2009. https://www.fda.gov/downloads/drugs/guidances/ucm193282.pdf 2017-01-01 3. Rothrock N, Kaiser K, Cella D. Developing a valid patient-reported outcome measure. Clin Pharmacol Ther, 2011;90:737–42